Serum biochemistry, fatty acids, lipid metabolism, antioxidants, and inflammation response were significantly affected by feeding different marine red yeast supplementation in juvenile tilapia (GIFT strain, Oreochromis niloticus) - Liu, Yongqiang; Huang, Enhao; Li, Ximiao; Xie, Yi; Meng, Liuqing; Liu, Dongsheng; Tong, Tong; Wang, Jinzi; Zhang, Qin (Frontiers in Marine Science, 2024)
Marine red yeast is a good feed additive for the aquaculture industry that can promote the growth of aquatic animals, and significantly improve their antioxidant capacity, survival rate, and nonspecific immune ability of the body. Our hypothesis is that dietary supplementation with marine red yeast could affect the serum biochemistry, muscle composition, muscle fatty acid composition, lipid metabolism enzyme activity, and expression of antioxidant and inflammatory genes in juvenile genetically improved farmed tilapia (GIFT, Oreochromis niloticus). Five diets with different levels of marine red yeast (0 %, 0.25 %, 0.50 %, 0.75 %, and 1.00 %) were used to feed juvenile GIFT (initial weight: 21.12 ± 0.86 g) for 60 days. The main results are as follows: Compared with the control group (0 % marine red yeast), the contents of total protein (TP), albumin (ALB), high-density lipoprotein (HDL), and free fatty acid (FFA) in the serum of juvenile GIFT tilapia significantly increased (P < 0.05), while the contents of glucose (GLU), triglyceride (TG), total cholesterol (T-CHO), low-density lipoprotein (LDL), alanine aminotransferase (ALT) significantly decreased (P < 0.05). The contents of crude protein, crude fat, and docosahexaenoic acid + eicosapentaenoic acid (DHA+EPA) in the muscle significantly increased (P < 0.05), while the contents of moisture and monounsaturated fatty acids (∑MUFAs) significantly decreased (P < 0.05). The activities of acetyl CoA carboxylase α (ACCα), glucose-6-phosphate dehydrogenase (G6PD), and stearoyl-CoA desaturase (SCD) in the liver significantly increased (P < 0.05). The expression levels of catalase (cat), alkaline phosphatase (alp), nuclear factor erythroid 2-related factor 2 (nrf2), lysozyme (lyz), glutathione S-transferase (gst), glutathione peroxidase (gsh-px), and superoxide dismutase (sod) genes in the liver significantly increased (P < 0.05). The expression levels of tumor necrosis factor α (tnf-α), interferon-γ (inf-γ), interleukin 6 (il-6), interleukin 8 (il-8), interleukin 1β (il-1β), and transforming growth factor-β (tgf-β1) genes in the liver, spleens, and head kidney significantly increased (P < 0.05), while the expression level of interleukin 10 (il-10) gene significantly decreased (P < 0.05). In conclusion, the addition of different levels of marine red yeast could significantly affect the serum biochemistry, muscle composition, muscle fatty acid composition, lipid metabolism enzyme activity, and expression of antioxidant and inflammatory genes in juvenile GIFT tilapia. Based on the results, the optimal dietary marine red yeast level was 0.50 %.